Some considerations on the concept of logic in Dewey's theory of inquiry and in Carnap's works on induction - Ferreira da Cunha, Ivan (Cognitio-Estudos: revista eletrônica de filosofia, 2012)
This paper aims to discuss some features of the concept of logic which can be found in John Dewey’s book Logic: The Theory of Inquiry in comparison with the concept of logic that underlies Rudolf Carnap’s semantical constructions, especially in the book Logical Foundations of Probability. John Dewey proposes in his book that logical forms – understood as the relation between arguments – arise within contexts of inquiry and are concerned with controlling inquiry. This is supposed to overcome the duality between logic and methodology of science, since logical constructions are to be derived from the process of scientific inquiry. This approach would also have the advantage of avoiding problems related to the foundations of logic, which frequently involve metaphysical positions and controversies. Carnap, on the other hand, adopts a method of abstraction for his constructions, that is, he seeks to develop a pure logic, avoiding getting into methodological problems. Dewey’s position apparently fails to account for the problem of psychologism and the matter of applications of logic, especially when considered in relation to the points of view presented in his later book Knowing and the Known, written with Arthur Bentley. This paper is going to discuss those two problems from Carnap’s point of view in order to reassess Dewey’s stance on that matter. Thus, we will see two conceptions of logic which apparently are opposed to each other, but it is intended to show that we are dealing with two different approaches with different scopes, and consequently they can and should be brought together in order to clarify epistemological problems.